The impact of the kinetics of games in some physical and motor abilities of volleyball players for ages ( 10-12 years) - Ibrahim, Khalil; Mahmoud, Shaker; Abedullah, Mahmoud (Journal of Physical Education, 2015)
The research aims to identify the impact of kinetic games in some physical and motor abilities between pretest and posttest for the two sets of research on the one hand and the preference kinetic games from the approach taken by the coach, and presumably search lies in the differences between tribal testing and dimensional difference in the post test between the two groups Search variables study. The researcher has used the experimental method to design the two groups Almtkavitin of a sample made up of 20 players from the National Center for the care of talented volleyball were divided into experimental groups and the control group and by 10 players per group, were tribal testing and then been applied games Kinetic Group and pilot included (12) Unit educational distributed (4) a week at a rate of (3) units per week using the kinetic games, and then after me test to see how much impact kinetic games on the physical and motor abilities procedure, and a time of 60 minutes for the unit, has been using kinetic games experimental group in The main section, and a time of (40) minute rest between game and other (2) minutes